A Visible‐Light‐Induced α‐H Chlorination of Alkylarenes with Inorganic Chloride under NanoAg@AgCl. Issue 27 (8th June 2015) - Liu, Shouxin; Zhang, Qi; Li, Huiying; Yang, Yihua; Tian, Xia; Whiting, Andrew
Abstract An efficient, photocatalytic chlorination of alkylarene α‐H groups using NaCl/HCl as a chlorine source has been developed, which involves a radical mechanism under visible‐light (including sunlight) conditions. A chlorine radical is proposed to be formed by an electron transfer from chloride ion to O2 in air through the bandgap hole of the semiconductor AgCl. The chlorination protocol is characterized by its use of natural sunlight or other visible light, mild conditions, cheap source of chlorine, green solvent, and high selectivity. The yield of benzylchloride is 95 % with a toluene conversion as high as 40 %, which rivals traditional chlorination methods.